Higher stability of oat, barley and wheat accessions in their 1000 grain weight is not associated with a smaller grain size - V. I. Polonsky; A. V. Sumina; S. A. Gerasimov; A. A. Kolichenko (Труды по прикладной ботанике, генетике и селекции)
Background. It is important and relevant to know whether the selection among cultivars for increased stability in the weight of 1000 grains involves a significant change in grain size.   The aim of the study was to analyze the relationship between the 1000 grain weight in oat, barley and wheat accessions, on the one hand, and their adaptability indicators for this trait, on the other.   Material and methods. The studied material included 10 cultivars of oat, 12 of barley, and 11 of wheat from the VIR collection. Plants were grown in 2021 at five different sites over Eastern Siberia (Krasnoyarsk Territory, and the Republic of Khakassia and Tyva). After harvesting, the weight of 1000 grains was measured for each cultivar. The coefficient of environmental variation (Cv), stress tolerance index (d), homeostasis parameter (Hom), stability level index (CSL), and breeding value index (Cs) were determined to assess the cultivars for the analyzed character.   Results. Oat cultivars exhibited significantly lower plasticity and higher stability in their 1000 grain weight. The best adaptability characteristics were recorded for oat cvs. ‘Argument’ and ‘Kross’, barley cvs. ‘Krasnoyarsky 91’ and ‘Biom’, and wheat cvs. ‘Novosibirskaya 49’ and ‘Novosibirskaya 75’. Cvs. ‘Kross’ and ‘Argument’ (oat). and ‘Biom’ (barley) had the largest grain size and maximum values of the character’s stability parameters. Correlations of oat and wheat grain size with both plasticity indices were negative, and positive with all stability parameters, being significant for CSL and Cs. In the case of barley cultivars, the correlation between the weight of 1000 grains and the plasticity index was negative and statistically significant.   Conclusion. The results demonstrate that when selecting oat, barley and wheat for increased stability of their 1000 grain weight, the grain size will not decrease. Moreover, it may have a tendency to increase.